O Modelo de gestão participativa do Plano Nacional do Turismo (PNT-2003/2007): a atuação do CONETUR/RN - Araújo, Regina Ferreira de (2008)
To implement policies and plans at the tourist sector involve disposition to the establishment of parceries among government and private initiative, space to the action of studious, researchers and professionals of several areas of knowledge and formation, able of to give new courses no only at the tourism, but to the economy how a every, seen which the tourism had a effect multiplicator, reaching 52 sectors of the economy. At this sense, the Brazil came pruning for a new phase of politic actuation at the touristy activity. Until the year 2002, the tourism politic in the Brazil no had detail, because herself treated of isolated actions and many without continuity. However, at to start 2003, several actions were developed in order to contribute for the national touristy planning. The principal was the creation of Ministério do Turismo, accompanied of the formulation and implementation of the Plano Nacional do Turismo (2003/2007). This work pretend to understand the implementation at the Rio Grande do Norte of the model of participative administration extolled by Plano Nacional do Turismo. The your centre detail the action of the Conselho Estadual de Turismo do Rio Grande do Norte (CONETUR), to promote the participation at the tourism public policies. The bibliographical research contemplated diverse sources in order to compile knowledge of credential authors in the quarrel of inherent subjects to the participation and to the tourism public policies, especially at the Brazil. A qualitative perspective the case study was adapted as research method and for attainment of the data interviews with the members of the Conselho had been carried through beyond consultation the referring documents the dynamics of functioning of the Conselho. The principal actuations of the CONETUR, the directives tourism public policies already made and directed to implementation, the type of participation at made decision, the principal difficulties of the implementation of the participative administration model of the Plano Nacional do Turismo and the degree of participation of the members of the Conselho at the reunions had been identified. The results had shown that exist some difficulties at the implementation of the participation at the Conselho Estadual de Turismo do Rio Grande do Norte, knowledge of the Conselheiros of CONETUR function, the presence of bodies which doesn t directly connected at the touristy activity; the absence of time of the Conselheiros to be presents at reunions; the discontinuity of the presidency of the Conselho; among others. So, the CONETUR show himself how a Conselho with participative characteristics, but with some adapted needs.